Photovoltaics: Reviewing the European Feed-in-Tariffs and Changing PV Efficiencies and Costs. (14th May 2014) - Zhang, H. L.; Van Gerven, T.; Baeyens, J.; Degrève, J.
Abstract : Feed-in-Tariff (FiT) mechanisms have been important in boosting renewable energy, by providing a long-term guaranteed subsidy of the kWh-price, thus mitigating investment risks and enhancing the contribution of sustainable electricity. By ongoing PV development, the contribution of solar power increases exponentially. Within this significant potential, it is important for investors, operators, and scientists alike to provide answers to different questions related to subsidies, PV efficiencies and costs. The present paper therefore (i) briefly reviews the mechanisms, advantages, and evolution of FiT; (ii) describes the developments of PV, (iii) applies a comprehensive literature-based model for the solar irradiation to predict the PV solar energy potential in some target European countries, whilst comparing output predictions with the monthly measured electricity generation of a 57 m² photovoltaic system (Belgium); and finally (iv) predicts the levelized cost of energy (LCOE) in terms of investment and efficiency, providing LCOE values between 0.149 and 0.313 €/kWh, as function of the overall process efficiency and cost. The findings clearly demonstrate the potential of PV energy in Europe, where FiT can be considerably reduced or even be eliminated in the near future.